Oscillatory nature in melt-gas-powder interactions during laser powder bed fusion process revealed by CFD-DEM coupled modelling - Weihao Yuan; Hui Chen; Siyuan Ruan; Rocco Lupoi; Shaocong Qin; Enyu Guo; Jianfeng Wang; Shuo Yin (Virtual and Physical Prototyping, 2025)
The laser powder bed fusion (LPBF) process encompasses interactions between different material states, including melt, gas, and powder. While observational techniques can capture specific states, they cannot be combined to produce a comprehensive monitoring how they are mutually interacted. Thus, an integrated modelling approach is a crucial solution for revealing their interactions. This study investigates melt-gas-powder dynamics under varying laser scan speeds through a coupled CFD-DEM multiphase model. Findings reveal that metal vapour consistently transitions from an initialisation phase to a processing phase, exhibiting consistent behaviour in the former but varied responses in the latter. A relationship is identified between scan speed and vapour flow angle (VFA), with higher speeds broadening the VFA. Significantly, three oscillatory behaviours are observed: first, the oscillation of locally intensified pressure (LIP) sites on keyhole walls, where vapour ejection modes shift and may become periodic at intermediate scan speeds; second, the oscillation of two induced argon vortex flows with opposite swirling directions; and third, a simultaneously induced varying drag force on powder spatter. These oscillations clarify various spatter mechanisms, offer insights for process optimisation, and suggest implications for process stability. The study also proposes future research directions to further elucidate these mechanisms.